The Brain-Heart Connection in Takotsubo Syndrome: The Central Nervous System, Sympathetic Nervous System, and Catecholamine Overload - Xiaopu Wang; Junyu Pei; Xinqun Hu (Cardiology Research and Practice)
Takotsubo syndrome (TTS), also known as stress cardiomyopathy, is a type of acute heart failure syndrome triggered by intense psychological or physiological stress. TTS typically manifests as acute chest pain, dyspnea or syncope that mimics an acute myocardial infarction but does not involve coronary artery obstruction. The current understanding of the pathogenesis of TTS suggests that sympathetic nervous system (SNS) activation plays a central role. Specifically, stress can activate the SNS and lead to the over-release of catecholamine, which have toxic effects on myocardial tissue when present at excessive levels. However, the brain changes associated with TTS and the connection between the brain and the heart in patients with this disease remain unclear. In recent years, several published reports have revealed the role of this brain-heart connection in the pathogenesis of TTS. This review summarizes recent studies regarding SNS activation, catecholamine overload, and the brain-heart connection in patients with TTS from both pathophysiological and mechanistic aspects.